PROVIDING QUALITY MONITORING OF EDUCATIONAL SERVICES IN HSEI OF UKRAINE «UMSA» - Zhdan, V.M.; Bobirev, V.M.; Bіlash, S.M.; Salіy, A.V.; Klimach, T.M. (World of Medicine and Biology, 2015)
The results of psychological research on adaptation, which was conducted among the students - first-year medical and dental faculty of Ukrainian Medical Dental Academy. It was found that the overall level of its teaching faculty - the faculty; providing students with the necessary training to literature; educational material and technical base; optimal scheduling sessions at a sufficient level. Freshmen satisfied with the quality of service and library reader hall. The students - freshmen HSEI of Ukraine "UMSA" supports the Bologna system of education. Most students do not want to change the training in the "YMCA" at another university. Adaptation of freshmen was successful. Stress factors that are most concerned about the students there - a significant amount of training load, an unusual schedule of classes, independent life. Active students - freshmen in extracurricular activities of the Academy is low, most are aware of it, but consider training a priority.
Keywords: adaptation; stress factors; the Bologna system of education; extracurricular activities